2019
DOI: 10.1371/journal.pone.0223575
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of commercially available endodontic bioceramic root canal sealers: A systematic review

Abstract: BackgroundRecently, a new generation of bioceramic root canal sealers has been introduced onto the market. Many in vitro studies have investigated the antimicrobial properties of these sealers, but their comparative efficacy in antimicrobial activity is still unknown.MethodologyThree electronic databases were searched: MEDLINE and Embase via the OvidSP platform, and Web of Science, up to June 25, 2019. Studies were included irrespective of study design, type of publication and language. Reporting quality was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 73 publications
(185 reference statements)
0
25
0
2
Order By: Relevance
“…2013, Šimundić Munitić et al . 2019), a biofilm aged 48 h was tested, because this period is sufficient to distinguish among the intracanal medicaments. Moreover, in relation to biofilm, it should be borne in mind that monospecies biofilms do not mimic the clinical situation as well as multispecies biofilm (Hoedke et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013, Šimundić Munitić et al . 2019), a biofilm aged 48 h was tested, because this period is sufficient to distinguish among the intracanal medicaments. Moreover, in relation to biofilm, it should be borne in mind that monospecies biofilms do not mimic the clinical situation as well as multispecies biofilm (Hoedke et al .…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have reported varying degrees of antimicrobial activity of bioceramic materials, precluding any conclusions to be drawn concerning its antimicrobial effectiveness (Šimundić Munitić et al . 2019). It is important to highlight that additional testing using a polymicrobial biofilm, dentine with a root canal geometry as a substrate (Swimberghe et al .…”
Section: Discussionmentioning
confidence: 99%
“…Endodontic bioceramics are not influenced by humidity or blood contamination [ 73 , 74 ], are stable and insoluble over time, providing an adequate seal [ 75 ]. Before setting, bioceramics manifest an antibacterial effect, and afterwards, they become biocompatible and bioactive [ 76 ]. Among these bioceramic endodontic materials, we can mention BioAggregate (Innovative Bioceramix, Vancouver, BC, Canada), with a composition similar to that of MTA’s.…”
Section: Introductionmentioning
confidence: 99%
“…According to the manufacturer, calcium silicate-based sealers such as Endosequence BC (Brasseler USA, Savannah, GA, USA) and iRoot SP (Innovative BioCeramix Inc., Vancouver, BC, Canada) are composed of calcium silicate, calcium phosphate, calcium hydroxide, zirconium oxide, and other agents [ 5 ]. They showed effective antimicrobial activity against multiple microorganisms [ 6 ]. Furthermore, they revealed a slight volume expansion while setting.…”
Section: Introductionmentioning
confidence: 99%